Transformation of Indonesia’s Licensing System: A Juridical Analysis of Risk-Based Approach Implementation in Practice - Donny Irawan; Francis Maryanne Pattynama; Fajar Pradita; Muhammad Idhom; Yanas Putra Prasadja; Narumi Hayakawa; Gyska Indah Harya (Kajian Ilmiah Hukum dan Kenegaraan, 2025)
Purpose: This study aims to analyze the legal basis, implementation, and challenges of Risk-Based Business Licensing (Perizinan Berusaha Berbasis Risiko/PBBR) as regulated in Government Regulation Number. 28 of 2025 in Indonesia. Methodology/Approach: This study employs a normative empirical approach. Normatively, it examines the administrative law principles underlying PBBR, whereas empirically it analyzes its implementation through the Online Single Submission (OSS) system and its impact on public service efficiency. Results/Findings: This study finds that PBBR represents a significant reform in Indonesian administrative law by applying the principles of proportionality, legal certainty, and public benefit. Empirically, its implementation has improved the efficiency of business licensing services, particularly through faster processing via the OSS system. However, several substantive and technical challenges remain, including inadequate digital infrastructure, overlapping regional and central regulations, and low legal literacy among micro and small business actors regarding risk classification and standard certification obligations. Conclusions: This study concludes that PBBR improves efficiency and legal certainty but is constrained by infrastructure, regulatory overlap, and low MSME legal literacy. Further improvements are needed. Limitations: This research is limited to regulatory analysis and selected empirical observations and does not include large-scale field surveys or quantitative measurement of business performance outcomes. Contributions: This study contributes to the development of administrative law and public policy literature by providing an integrated analysis of risk-based licensing reform in Indonesia and offering practical recommendations for improving institutional capacity and regulatory harmonization.